Microbial Communities Associated With Indigo Fermentation That Thrive in Anaerobic Alkaline Environments - Aino, Keiichi; Hirota, Kikue; Okamoto, Takahiro; Tu, Zhihao; Matsuyama, Hidetoshi; Yumoto, Isao (Frontiers in Microbiology, 2018)
Indigo fermentation, which depends on the indigo-reducing action of microorganisms, has traditionally been performed to dye textiles blue in Asia as well as in Europe. This natural fermentation process is carried out by naturally occurring microbiota and proceeds under alkaline anaerobic conditions. For these reasons, there is uncertainty about the fermentation process, and many unknown microorganisms thrive in this special fermentation environment. Limited information had been available on the indigo-reducing bacteria that performs indigo fermentation until recently. Indigo reduction normally occurs from the 4th day to 2 weeks after initiation of the fermentation preparation. Indigo reduction is assumed to occur due to the appearance of indigo-reducing microorganisms. However, changes in the microbiota in the transition to an indigo-reducing state have not been clarified. Here, the structural changes in the bacterial community were estimated via PCR-based methods. On the second day of fermentation, a large change in the redox potential occurred. On the fourth day, pronounced substitution of the aerobic genus Halomonas with the aerotolerant genus Amphibacillus was observed, corresponding to marked changes in indigo reduction. Indigo reduction during the fermentation process continued for 6 months on average. Identification of the long-lasting mechanism underlying this fermentation process under open-air conditions would be quite intriguing. To clarify the mechanism, we estimated changes in the microbiota in fermentation fluids maintained in a reducing state for more than 6 months. The results showed that the microbiota, including indigo-reducing bacteria, were continuously replaced by other microbiota consisting of other types of indigo-reducing bacteria. A stable state consisting mainly of the genus Anaerobacillus was also observed in a long-maintained fermentation sample. It appears that the stability, the existing ratio of indigo-reducing microorganisms and the appropriate diversity of microbiota play key roles in maintaining a state of reduction in long-term indigo fermentation.